Numerical simulation of dynamic object based on convolution operations - Sterten, Jo (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2016)
A recursive digital filter construction method is considered for simulation of inertial element as a typical component of complex dynamic object. New computational formulas are obtained. Their high accuracy as compared to traditional ones is shown. Decomposition of initial model of simulated object by convolution operations with several typical exponential kernels is proposed instead of traditional operations of integration and differentiation.